Abundance and movements of caribou in the oilfield complex near Prudhoe Bay, Alaska - Cameron, R.D.; Lenart, E.A.; Reed, D.J.; Whitten, K.R.; Smith, W.T. (Rangifer, 1995)
We examined the distribution and movements of 141 radiocollared female caribou (Rangifer tarandus granti) of the Central Arctic Herd during summer, 1980-1993. Numbers of caribou locations within each of 5 quadrats along the arctic coast were totalled separately for days during which insects were active and inactive, and numbers of east-west and west-east crossings of each quadrat mid-line were determined from sequential observations. Both abundance and lateral movements of radiocollared females in the quadrat encompassing the intensively-developed Prudhoe Bay oilfield complex were significantly lower than in other quadrats (P < 0.001 and P < 0.00001, respectively). Avoidance of, and fewer movements within, the complex by female caribou are ostensibly in response to the dense network of production and support facilities, roads, above-ground pipelines, and the associated vehicular and human activity. Impaired access to this area constitutes a functional loss of habitat.